CONTEXTUAL GROUP GUIDED DISCOVERY LEARNING (International Conference on Elementary Education, 2018)
Contextual Group Guided Discovery (CGGD) is a learning approach developed based on the philosophy of social-constructivist. This approach developed to support teacher in designing lesson with creating a learning environment that builds students competence required for 21st-century skills. We develop this learning approach by collaborating on principles of 1) contextual teaching, 2) Collaborative learning, and 3) Guided discovery learning. This learning approach developed using research and development (R&D) procedure of ADDIE (Dick & Carry, 1996). The result from our study is a syntax that describes all about CGGD learning approach.